Зимняя девочка: повесть, рассказы / С. А. Иванов - Иванов Сергей Анатольевич (Репро, 1999)
Экземпляры: БС (20170724) / Инвентарный номер: РТШ49159 / Сис.шифр: Р2 / Авт.знак: И 20 / ГРНТИ: 17 / ББК: 84(2)